The Strength of Mortar Mixed with Polystyrene Beads - Ruslan, Nur Nabilah; Mohd Jahari, Nur Aina; Abdullah, 'Aqilah Nabihah (Multidisciplinary Applied Research and Innovation, 2023)
The use of polystyrene beads as a lightweight aggregate in cement mortars is the subject of this research. This is because fully mortar has issues such as being heavy, leaking, and mossy due to high water absorption. The purpose of this research is to look at the qualities of the proposed good water absorption and high strength lightweight concrete mix. The replacement of construction material for mortar roof tiles have been conducted with replacement of 0% as control sample, 5%, 10% and 15% as new sample with polystyrene beads. Concrete slump test, cube preparation, curing process and compressive strength test were performed. The material that was used to complete this research is cement mortar, fine aggregates and polystyrene beads. The outcomes were compared on the amount of material mixture and testing day. It’s interesting to learn that polystyrene beads mixed with concrete mortar have an impact on compressive strength and water absorption. Polystyrene beads is strongly suggested for future research as a micture with mortar concrete.